Open Access Indian Publications: An Empirical Study of DOAJ - Panda, Subhajit (Journal of Information and Knowledge, 2021)
There are two general strategies for achieving Open Access (OA) to scholarly communication, the gold road and the green road. The largest and authoritative gold road OA database is the Directory of Open Access Journals (DOAJ) indexing all the standard OA journals meeting the DOAJ criteria of inclusion. The purpose of this paper is to investigate the contribution of Indian publications to the global OA movement. The analysis of the present study was done based on a total dataset of 289 research publications of Indian OA journal as imported from the DOAJ database. The findings of the study reveal that Indian OA journals account for only 2% of the total coverage of DOAJ. Among them, journals in the field of Medicine alone account for 79% and approximately 73% of journals are published in both print & electronic medium with PDF as the preferred file format, DOI as preferred permanent article identifier and English as the preferred language of publication. Almost 89% of Indian OA journals provide full-text crawl permission, while 75% of them provide download statistics. All the Indian journals covered under DOAJ are peer-reviewed and out of them, most of the journals (76%) are double-blind peer-reviewed. Indian OA publications with CC BY-NC-SA license cover the highest percentage (75%) and 206 journals (71%) do not charge APC. In majority of Indian OA journals (89%), the author doesn’t hold either the copyright or publishing rights without restrictions from the journal publishers. It is important to note that only two journals (~1%) satisfied the requirements of DOAJ Seal.